Protective effect of the novel calcineurin inhibitor voclosporin in experimental colitis - Lindemann, Aylin; Roth, Dominik; Koop, Kristina; Neufert, Clemens; Zundler, Sebastian; Atreya, Raja; Neurath, Markus F.; Leppkes, Moritz (Frontiers in Medicine, 2023)
Background and Aims: Acute severe steroid-refractory ulcerative colitis remains a medically challenging condition with frequent need of surgery. It can be treated with the calcineurin inhibitor cyclosporine A with the need for therapeutic drug monitoring and significant toxicity. Recently, a novel calcineurin inhibitor, voclosporin, has been approved for the treatment of lupus nephritis with no need for therapeutic drug monitoring and an improved long-term safety profile. We aimed to assess the therapeutic potential of voclosporin to ameliorate inflammation in an experimental model of colitis. Methods: We used the dextran sodium sulfate-induced model of colitis in C57BL/6J wildtype mice treated with either cyclosporine A, voclosporin or solvent control. We employed endoscopy, histochemistry, immunofluorescence, bead-based multiplex immunoassays and flow cytometry to study the therapeutic effect of calcineurin inhibitors in a preventive setting. Results: Acute colitis was induced by dextran sodium sulfate characterized by weight loss, diarrhea, mucosal erosions and rectal bleeding. Both cyclosporine A and voclosporin strongly ameliorated the course of disease and reduced colitis severity in a similar manner. Conclusions: Voclosporin was identified as biologically effective in a preclinical model of colitis and may be successfully developed in clinical studies of patients with acute severe steroid-refractory ulcerative colitis.